Spider Assemblages across Elevational and Latitudinal Gradients in the Yukon Territory, Canada - Bowden, J.J.; Buddle, C.M. (ARCTIC, 2010)
Arthropod assemblages in the Arctic are set for substantial changes in response to climate change, yet we know little about the ecological structure of many groups in the North. We tested the effects of elevation and latitude on northern spider assemblages by sampling along nine mountains across three latitudes in the Yukon Territory, Canada. Spiders were collected in 216 pitfall traps placed at four elevations along each of the nine mountains, representing 36 sites sampled across three latitudes (i.e., distinct mountain ranges). We collected 1954 individuals representing 89 species, 57 genera, and 12 families of spiders. Using nested ANOVAs, we found significant main effects of latitude, elevation, and an interaction of the two factors on species richness and abundance. Using MRPP and NMS ordination, we also found significant effects of latitude and mountain on species composition, but within each of the three latitudes, only elevation produced significant effects. Our study suggests that changes along spatial gradients associated with changes in habitat can have significant effects on the structure of spider assemblages, but responses vary among mountain ranges. We show that within a given mountain range, individual mountains may be used as spatial replicates for studies about northern arthropod assemblages. Les assemblages d’arthropodes de l’Arctique connaîtront des changements substantiels en raison du changement climatique mais malgré cela, nous en savons peu sur la structure écologique de nombreux groupes du Nord. Nous avons mis à l’épreuve les effets de l’élévation et de la latitude sur les assemblages d’araignées du Nord en prélevant des échantillons sur neuf montagnes réparties sur trois latitudes dans le territoire du Yukon, au Canada. Les araignées ont été recueillies à l’aide de 216 pièges placés à quatre élévations différentes le long de chacune des neuf montagnes, ce qui a représenté 36 emplacements échantillonnés sur trois latitudes (c’est-à-dire des chaînes de montagnes distinctes). Nous avons ...